2012
DOI: 10.1111/j.1551-2916.2012.05465.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Mechanical Evaluation of Bioactive Glass 45S5 Foams Obtained by a Powder Technology Approach

Abstract: Bioactive glass 45S5 foams were produced using a powder technology process developed by The National Research Council Canada-Industrial Materials Institute. NRC-IMI's proprietary process, combining powder technology and polymer foam technique, allows the production of materials having different structures and properties. It can be used to produce components into various forms, such as fully porous bodies or coatings on solid structures. During foaming, the foaming agent is decomposed and expands the binder-bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 24 publications
(37 reference statements)
2
25
1
Order By: Relevance
“…The compressive strengths are Ceramics International xxx (xxxx) xxx-xxx low, compared with the value obtained in the present work, even those reported for scaffolds with less porosity, with the exception of the strengths reported by Wu et al [38]. This compressive strength improvement in scaffolds prepared using mixed powder technology and the polymer foaming method may be associated with the consolidation of the struts within the structure of the foams, because the particles are better sintered as the sintering temperature increases [10]. This leads to a decrease in porosity between struts and particles, with the resulting increase in the mechanical properties of the structure.…”
Section: Ea Aguilar-reyes Et Alcontrasting
confidence: 53%
See 1 more Smart Citation
“…The compressive strengths are Ceramics International xxx (xxxx) xxx-xxx low, compared with the value obtained in the present work, even those reported for scaffolds with less porosity, with the exception of the strengths reported by Wu et al [38]. This compressive strength improvement in scaffolds prepared using mixed powder technology and the polymer foaming method may be associated with the consolidation of the struts within the structure of the foams, because the particles are better sintered as the sintering temperature increases [10]. This leads to a decrease in porosity between struts and particles, with the resulting increase in the mechanical properties of the structure.…”
Section: Ea Aguilar-reyes Et Alcontrasting
confidence: 53%
“…The 45S5 bioactive glass scaffolds were produced through the combination of powder technology and the polymer foaming method [10]. The glass powder was dry-mixed with a solid polymeric binder (Varcum 29217, Durez Corporation, Niagara Falls, NY, USA) and a foaming agent (p-toluenesulfonyl hydrazide or TSH, Sigma-Aldrich, St. Louis, MO, USA) at a ratio of 45/54.5/0.5 in wt%, respectively.…”
Section: Fabrication Of 45s5 Bioglass® Glass Scaffoldsmentioning
confidence: 99%
“…In recent years, 3D Bioglass based foams have been produced using a powder technology process developed by the National Research Council Canada-Industrial Material Institute. 23,24 Aguilar-Reyes et al showed that foams with interconnected porosity (64-79% porosity) and with open pores in the 100-800 mm range can be produced with this process. The foams produced showed good mechanical strength (1.7-5.5 MPa) comparable with the compression strength of cancellous bone (2-12 MPa).…”
mentioning
confidence: 99%
“…23,24 One difficulty is the fabrication of a scaffold that has the same high porosity and sufficient mechanical strength and stability as natural bone. One approach could be the manufacture of Bioglass based scaffolds with enhanced mechanical properties by reducing the total porosity but without detrimentally affecting the pore interconnectivity.…”
mentioning
confidence: 99%
“…[37][38][39] Initially, the glass powder was drymixed with a solid polymeric binder (Varcum 29217) and a foaming agent (p-toluenesulfonyl hydrazide) at a 45/54.5/ 0.5 ratio in wt%, respectively. The 45% SiO 2 , 3% P 2 O 5 , 26% CaO, 7% MgO, 15% Na 2 O, 4% K 2 O (Sigma Aldrich) molar composition was mixed and the powders were placed on a fused silica crucible.…”
Section: Fabrication Of the Cel2 Bioactive Glassceramic Scaffoldsmentioning
confidence: 99%